Characteristics of stone raw materials in medieval churches in Kołbaskowo commune - Cedro, Bernard (Acta Geographica Lodziensia, 2023)
The article presents the characteristics of rock material used as a building material in medieval stone churches. Macroscopic petrographic analysis showed that the rock blocks used for the construction of medieval churches in the Kołbaskowo commune were generally made of material available on site. They were rocks originating from Fennoscandia but extracted from sediments deposited by ice sheets that had advanced in from the north. The obtained results were compared against macroscopic analyses of the petrographic composition of Scandinavian erratic boulders in the area and accumulations of raw material in megalithic objects. The results of petrographic observations made it possible to distinguish the basic types of rock materials used in the construction of the churches. The most commonly used materials were: granitoids, gneisses, rhyolithoids, sandstones and quartzites. All the churches built in the 13th century within what is today Kołbaskowo commune show a predominance of granitoids.